Kompensasi Dalam Meningkatkan Kinerja Karyawan PT. Asuransi Sinar Mas - Ferdian Arie Bowo; Ratna Kusuma Dewi (Manajerial, 2020)
The aims of this research to analyze and examine the important factors in HR planning to sustain the company’s existence in advancing quality and performance, namely the provision of compensation. The research method used is the quantitative associative survey research method. The population in this study were all employees at PT. Sinar Mas Insurance. With a sample of sixty seven employees. This research was conducted at PT. Sinar Mas Insurance. The finding of this research indicate that the effect of compensation on performance has a contribution of 26.01%, while the other 63.99% is determined by other factors not included in this research. The conclusion of this research shows that a good compensation system will improve employee performance.